Penerapan Model Pembelajaran Inquiry Berbantuan Media Handout Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Struktur Atom Kelas X SMA - Napitupulu, Even; Simanjuntak, Hendra; Manurung, Hisar Marulitua (UNIB Press, 2025)
This study aims to determine the effect of implementing the inquiry learning model assisted by handout media to improve student learning outcomes in atomic structure material for class X of SMA Negeri 1 Girsang Sipanganbolon. The type of research used is a quasi-experimental study with a pretest-posttest control group design. The research subjects consisted of two classes, namely the experimental class that received learning with inquiry learning models assisted by handout media and the control class that received conventional learning. The research instrument was a learning outcome test given before and after treatment. Data were analyzed using t-test and N-Gain calculations. The results showed that the average pretest scores of both classes were relatively the same. After learning, the average post-test score of the experimental class increased higher than the control class. The average N-Gain score of the experimental class was at 54% in the quite effective category, while the control class was at 21% in the ineffective category. The results of the t-test showed a significance value of p <0.05, which means there was a significant difference between the learning outcomes of the two classes. Thus, it can be concluded that the application of the inquiry learning model assisted by handouts improves student learning outcomes in atomic structure.